2010
DOI: 10.1371/journal.pone.0013151
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Porin/VDAC Affects Mitochondrial Morphology

Abstract: Voltage-dependent anion channel (VDAC) has been suggested to be a mediator of mitochondrial-dependent cell death induced by Ca2+ overload, oxidative stress and Bax-Bid activation. To confirm this hypothesis in vivo, we generated and characterized Drosophila VDAC (porin) mutants and found that Porin is not required for mitochondrial apoptosis, which is consistent with the previous mouse studies. We also reported a novel physiological role of Porin. Loss of porin resulted in locomotive defects and male sterility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…6). These modifications of mitochondrial morphology in Arabidopsis are similar to the ones described in muscles of mouse (Anflous et al 2001;Sampson et al 2001) and in drosophila (Graham et al 2010;Park et al 2010). They are often associated with cell death, in particular during necrosis in plants (van Doorn et al 2011), and could explain the presence of yellow spots and the high production of ROS in atvdac1 and atvdac4 leaves (Fig.…”
Section: Absence Of Atvdac1 Atvdac2 and Atvdac4 Proteins Results In supporting
confidence: 76%
“…6). These modifications of mitochondrial morphology in Arabidopsis are similar to the ones described in muscles of mouse (Anflous et al 2001;Sampson et al 2001) and in drosophila (Graham et al 2010;Park et al 2010). They are often associated with cell death, in particular during necrosis in plants (van Doorn et al 2011), and could explain the presence of yellow spots and the high production of ROS in atvdac1 and atvdac4 leaves (Fig.…”
Section: Absence Of Atvdac1 Atvdac2 and Atvdac4 Proteins Results In supporting
confidence: 76%
“…As summarized by [73], VDAC interactions with different proteins contribute to apoptosis, cytoskeleton functions, Ca 2+ and oxidative-redox homeostasis as well as energy transformation (Figure 2). There are also data pointing at interaction between VDAC and mitochondrial trafficking and fusion/ fission machinery [74,75]. Consequently, VDAC modulation may affect processes that are known to be affected by VDAC directly; i.e., the respiratory chain, transcriptional regulation and protein import, Ca 2+ balance, oxidative stress and apoptosis, or might be affected due to interaction between VDAC and the involved proteins.…”
Section: Vdac As a Versatile Proteinmentioning
confidence: 99%
“…Numerous experiments have been conducted examining localization, identification, and expression of VDACs in spermatozoa (8,9,(22)(23)(24)(25)(26)(27)(28), and Liu et al (26,28) reported that VDAC expression was related to sperm motility. Nevertheless, the roles of VDACs in spermatozoa during reproduction are not yet fully understood.…”
mentioning
confidence: 99%